The effect of the interosseous ligament and selected antebrachiocarpal ligaments on rotation of the radius during extension of the carpus. Issue 5 (13th February 2021) - Atamna, Raya; Bitton, Erez; Shemtov, Yael; Segev, Gilad; Shipov, Anna; Milgram, Joshua
Abstract: Objective: To evaluate the effect of the interosseous ligament and selected antebrachiocarpal ligaments on the internal rotation of the radius relative to the ulna, during carpal extension. Study Design: Cadaveric study. Sample population: Twenty‐four cadaveric canine forelimbs. Methods: Twenty‐four forelimbs were disarticulated at the elbow joint and the antebrachia were prepared for testing. The forelimbs were divided to 6 groups, defined by the order in which ligaments were transected. All specimens were tested intact and after transecting each of the ligaments with the order defined by the group. Rotation of the radius relative to the ulna, caused by extension of the carpus, was measured using a sensor connected to the radius. Results: The mean(±sd) maximum internal rotation of the radius (5.94° ± (1.23°)) with all the ligaments intact was significantly greater (p < 0.012) than the mean(±sd) maximum internal rotation of the radius (3.13° (± 1.13°)) after transecting the interosseus ligament. Transecting the interosseous ligament subsequent to one of the other ligaments caused a decrease in internal radial rotation (p = 0.629), while, transecting the short radial collateral ligament caused an increase in radial rotation (p = 0.629). Transecting the palmar radiocarpal and ulnocarpal ligaments had no effect on radial rotation. Conclusion: The interosseous ligament was stretched with internal rotation of the radius due to carpal extension. Carpal flexion resulted in external rotation of the radius. This effect was lost when the interosseus ligament was transected. Clinical Significance: Rotation of the radius is associated with carpal extension, and is likely an intrinsic part of forelimb biomechanics.